2013
DOI: 10.18632/oncotarget.1699
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the vacuolar ATPase induces Bnip3-dependent death of cancer cells and a reduction in tumor burden and metastasis

Abstract: The pro-apoptotic protein Bnip3 is induced by hypoxia and is present in the core regions of most solid tumors. Bnip3 induces programmed necrosis by an intrinsic caspase independent mitochondrial pathway. Many tumor cells have evolved pathways to evade Bnip3-mediated death attesting to the physiological relevance of the survival threat imposed by Bnip3. We have reported that acidosis can trigger the Bnip3 death pathway in hypoxic cells therefore we hypothesized that manipulation of intracellular pH by pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 61 publications
7
40
1
Order By: Relevance
“…Graham RM et al show that the inhibition of the vacuolar ATPase induces a reduction in tumor burden and metastasis in breast cancer. 47 Overall, our results stress that acidosis of tumor microenvironment potentiates the pro-tumoral activity of MSC, representing a reasonable target for melanoma.…”
Section: Discussionmentioning
confidence: 51%
“…Graham RM et al show that the inhibition of the vacuolar ATPase induces a reduction in tumor burden and metastasis in breast cancer. 47 Overall, our results stress that acidosis of tumor microenvironment potentiates the pro-tumoral activity of MSC, representing a reasonable target for melanoma.…”
Section: Discussionmentioning
confidence: 51%
“…Again, no toxic side effects were observed using baf‐A1 (1 mg/kg). Additionally, when combined with sorafenib, it was shown that V‐ATPase treatment could result in tumor regression in MDA‐MD‐231 xenograft mice 86. Another study demonstrated that growth of a HepG2 orthotopic HCC xenograft model in nude mice was retarded by baf‐A1 42…”
Section: V‐atpase As a Potential Cancer Therapeutic Targetmentioning
confidence: 99%
“…TM9SF4/V-ATPase interaction: a key event in tumor pH gradient F Lozupone et al TM9SF4 silencing inhibits tumor cell invasiveness Extracellular acidity increases local invasiveness of cancer cells, and a number of studies have suggested that a key role in cell invasion is played by V-ATPase expressed on the cell surface. 8,[28][29][30][31] We thus investigated the migration and invasiveness of SCR and TM9SF4-KD cells. Migration was assessed by scratch test and by 8 μm pore size Boyden chamber-based assay, whereas invasiveness was evaluated in an assay based on the utilization of Matrigel-coated Boyden chambers.…”
Section: Tm9sf4 Colocalizes With V-atpase In Colon Cancer Cellsmentioning
confidence: 99%